Unit Cell Optimization of Groove Gap Waveguide for High Bandwidth Microwave Applications - Ghiayas Tahir; Arshad Hassan; Shawkat Ali; Amine Bermak (Applied Sciences)
Recently, groove gap waveguides (GGWs) have shown significant potential in power handling and bandwidth enhancement compared to conventional waveguides. In this research work, we designed and developed an innovative mushroom-unit-cell-based groove gap waveguide (MGGW) that has shown improved bandwidth compared to conventional GGW structures. The dispersion characteristics of the MGGW were analyzed through the eigenmode solver feature of Microwave Studio CST, which showed that the bandwidth was improved by 8% compared to conventional unit cells in the microwave spectrum. To validate our proposed method for the physical dimensions of unit cell structures, we developed an MGGW structure for the S band, which shows similar trends aligning with the simulation results. The measurement results are promising as a reflection coefficient of less than −20 dB was achieved over the entire band for the WR284 Electronic Industries Alliance (EIA) standard waveguide adapter. The proposed MGGW structure with improved bandwidth will open new doors for researchers to develop ultra-wide bandwidth microwave applications, i.e., filters, transmission lines, resonators, attenuators, etc.